Crecimiento de las plantas de tres especies forestales con aplicación de abonamiento foliar en plantación. Puerto Almendra, Loreto, Perú – 2021 - Arévalo Cardenas, Grecia (2022)
The thesis was developed at the facilities of CIEFOR Puerto Almendra FCF - UNAP, San Juan Bautista, Maynas, Loreto, Peru. The objective was to determine the effect of foliar fertilization on growth in height and diameter of plants of three forest species in plantation with foliar fertilization. Plots 5 were used: strips "A", "C", "E", "H", "J", "K" and Plot 2: strips "A", "D", "H" of the plantation; foliar fertilization of 10 ml / 200 ml of water. The results show that the increase in diameter and total height had the same trend, being the Cedrelinga cateniformis "tornillo" the one that presented the highest values with 124 cm in total height and 13,3 mm in diameter, followed by the Swietenia macrophylla "caoba" with 91 cm in total height and 12,2 mm in diameter, finally the Cedrela odorata “cedro” with 77 cm in total height and 9 mm in diameter; but according to the statistical analysis there is no significant difference in the increases in diameter and total height between the three forest species evaluated with 95% confidence.